Assessing the effects of concussion using the C3Logix Test Battery: An exploratory study. Issue 3 (4th May 2019) - Bernstein, John P. K.; Calamia, Matthew; Pratt, Joshua; Mullenix, Shelly
ABSTRACT: The C3Logix is a computerized concussion assessment tool that measures a wider array of symptoms (i.e., balance and oculomotor functioning) than other computerized batteries. Although the C3Logix has been used increasingly by athletic organizations at all levels of play, its utility within the concussion population has not been extensively examined. The current study aimed to determine whether the C3Logix is sensitive to the effects of concussion. A total of 54 student-athletes enrolled at a large southern university completed the C3Logix at baseline and within days following a suspected concussion (mean = 2.93, SD  = 3.14). Dependent-samples t -tests revealed that relative to their baselines, following concussion, athletes both reported significantly greater postconcussive symptoms and performed more poorly on measures of reaction time and computer-measured balance. Decrements in processing speed, visual acuity, and clinician-observed errors on tests of balance also trended toward significance. Results suggest that inclusion of measures of balance and oculomotor functioning in the assessment of concussion may provide additional clinical utility above and beyond domains typically measured by computerized concussion assessments.